Idylle & Katastrophe : Neoakademismus und nekrorealismus aus Sankt Petersburg. - EKTachrom - Europäisches Kulturzentrum und Kunst, Erfurt; Andreeva, Ekaterina; Artjuch, Anzhelika; Mazin, Viktor; Rothamel, Jörk; Turkina, Olesja (Erfurt : EKTachrom - Europäisches Kulturzentrum und Kunst, 1996)
Barov, Andrej ; Bujvid, Viktorija ; Egelskij, Denis ; Goncharov, Konstantin ; Jufit, Evgenij ; Kustov, Vladimir ; Kuznecov, Viktor ; Maslov, Oleg ; Novikov, Timur ; Ostrov, Egor ; Sokolov, Aleksej ; Tobreluts, Olga ; Uchalova, Viktorija
biografie
Idylle & Katastrophe : Neoakademismus und nekrorealismus aus Sankt Petersburg, EKTachrom - Europäisches Kulturzentrum und Kunst, Erfurt, 22.3. - 21.4.1996
Duits
boek